2002
DOI: 10.1002/cne.10304
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gonadal steroid treatment and peripheral nerve grafting results in a peripheral motoneuron‐like pattern of BII‐tubulin mRNA expression in axotomized hamster rubrospinal motoneurons

Abstract: Rubrospinal motoneurons (RSMN) represent a population of androgen receptor-containing central motoneurons in rodents. In this study, the ability of testosterone propionate (TP), alone or in conjunction with a peripheral nerve graft (PNG), to alter the molecular program of injured RSMN was accomplished using betaII-tubulin cDNA probes and quantitative in situ hybridization (ISH). Initial fluoro-gold labeling experiments following a T1 hemisection established that, as in the rat, the hamster rubrospinal system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…However, recent studies of motoneuron diseases in the mouse indicate that axonal defects in growth and maintenance, such as microtubule assembly, RNA processing, and axonal transport, have profound implications on motoneuron viability (Jablonka et al, 2004). The work that we have accomplished to date demonstrates that steroid regulation of neuronal injury and repair involves ribosomal RNA processing (Kinderman and Jones, 1993;Storer and Jones, 2003) and tubulin expression (Jones and Oblinger, 1994;Storer et al, 2002), which, together with the results of the present study, link the pathways for survival and axonal elongation after direct trauma. Future directions include investigation of ER-␣ and ER-␤ expression in developing hamster FMNs using both immunocytochemistry and Western blot techniques and utilization of this model system for the investigation of cellular mechanisms related to motoneuron disease.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, recent studies of motoneuron diseases in the mouse indicate that axonal defects in growth and maintenance, such as microtubule assembly, RNA processing, and axonal transport, have profound implications on motoneuron viability (Jablonka et al, 2004). The work that we have accomplished to date demonstrates that steroid regulation of neuronal injury and repair involves ribosomal RNA processing (Kinderman and Jones, 1993;Storer and Jones, 2003) and tubulin expression (Jones and Oblinger, 1994;Storer et al, 2002), which, together with the results of the present study, link the pathways for survival and axonal elongation after direct trauma. Future directions include investigation of ER-␣ and ER-␤ expression in developing hamster FMNs using both immunocytochemistry and Western blot techniques and utilization of this model system for the investigation of cellular mechanisms related to motoneuron disease.…”
Section: Discussionsupporting
confidence: 64%
“…Adult hamster peripheral and central motoneurons respond with enhanced regenerative properties when steroids are exogenously administered, in supraphysiological levels, at the time of injury (Storer et al, 2002;Storer and Jones, 2003). After facial nerve injury in the adult hamster, both androgens and estrogens accelerate the rate of facial nerve regeneration (Tanzer and Jones, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…While α Itubulin, β II -tubulin, and β III -tubulin are all upregulated by axotomy, only β II -tubulin has been shown to be under the control of androgen in this model (Jones and Oblinger, 1994;Jones et al, 1999b). Tubulin genes are also regulated by androgen in axotomized sciatic motoneurons ) and rubrospinal motoneurons (Storer et al, 2002;DeLucia et al, 2007), and in the spinal nucleus of the bulbocavernosus (SNB; Matsumoto et al, 1993Matsumoto et al, , 1994, a group of motoneurons whose dendritic extension and retraction is under the control of androgens (Fargo and Sengelaub, 2007b;Kurz et al, 1986), raising the possibility that this may be a general phenomenon in motoneurons.…”
Section: Cellular and Molecular Mediatorsmentioning
confidence: 72%
“…We have begun exploring the possibilities of using androgens as an adjuvant therapy in several experimental paradigms with translational implications. We have combined testosterone treatment with other therapies, including grafting of peripheral nerves into the injured spinal cord, to enhance the expression of cytoskeletal genes in injured rubrospinal motoneurons (Storer et al, 2002;DeLucia et al, In press). We have also shown that testosterone treatment enhances the ability of electrical stimulation to increase peripheral axon regeneration rates (Lal et al, 2007;Hetzler et al, 2007), and are applying that to clinical situations in which the facial nerve is damaged following acoustic neuroma formation.…”
Section: Future Directionsmentioning
confidence: 99%
“…This regenerative failure is due to both intrinsic (e.g., gene expression) and extrinsic (e.g., environmental) factors. This stands in contrast to the regeneration that readily occurs in the peripheral nervous system (Seijffers et al, 2007), when the CNS axons are injured during early development (Moore et al, 2009;Blackmore et al, 2010), or when a peripheral nerve is apposed to severed axons in the adult CNS (Richardson et al, 1980;David and Aguayo, 1981;Storer et al, 2002;Campbell et al, 2005;Houle et al, 2006;Tom et al, 2009).…”
mentioning
confidence: 86%